Maklumat perioperatif yang diterima dan tahap kecekapan kendiri pesakit Yang menjalani surgeri dl Hospital Universiti Sains Malaysia - Mustapa, Azilah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2008)
Surgery is an aversive situation which leads to emotional distress. It is regarded with fear, anxiety, loss of control and low self-esteem among surgical patients. Perioperative infonnation is one of the ways to help people cope with the stress of surgery and it is one of the important roles of a nurse. There were a lot of previous studies revealed that perioperative information leads to positive outcomes. Information alone however, is not sufficient to ensure the actual performance of postoperative behaviors. Self-efficacy is one of the factors that may contribute to patient's decision to perf01m given information in the form of behaviors. Thus, the purposes of this study were to determine the perioperative information received and the level of self- efficacy among surgical patients in Hospital University Science Malaysia (HUSM). The subject were selected using non - probability purposive sampling. The subject included 65 surgical patients which met the inclusion criteria. The result shows that perioperative information received was inconsistent. There were only 7 infonnation received by all patients which were; information regarding waiting area for family and fiiends during surgery (l 00%), sensation that will perceived by patient after taking the medication given before surgery (I 00%), when patient will be allowed to eat and drink after surgery (I 00%), anesthesia that patient will receive ( l 00%), routine procedure before going to operation theater (I 00%), procedure performed by nurses day before surgery ( I 00%) and date and time of surgery (I 00%). In contrast, the least infonnation received by patient was information regarding non-pharmacological method to reduce pain (2%). Next, tllis study revealed that surgical patients had a high level of selfefficacy (M = 4.11 , SD = 0.4 7). Furthennore, this study shows that there was a significant relationship between gender and self- efficacy (p = 0.0 16). Thus, this study purposed that a guideline regarding the contents of perioperative information need to be developed to ensure all surgical patients receive standard and sufficient information. Moreover, it needs to be provided in the fonn of efficacy enhancing way to increase the level of confidence among patients. This will help to increase the quality of patient care in HUSM.